Enhancing Dental Health Awareness Among Santri Through the Role of Livestock Farming Families and Local Entrepreneurs in Supporting Sustainable Tourism in Pangandaran - Nurhamsyah, Donny; Mutaqin, Bambang Kholiq; Maziyya, Nur; Supriat, Didin; Fitri, Siti Yuyun Rahayu (Unpad Press, 2025)
Increasing awareness of oral health among students at Pondok Pesantren Asy-Syujaa’iyyah in Cintaratu Village, Pangandaran, is essential for supporting sustainable tourism development. Children from farming families and local business owners often have limited access to dental services, leading to common issues such as cavities and gum problems. This community service initiative aims to enhance students' understanding of the importance of oral health through education and free dental check-ups. The program involved 111 students, 63.1% of whom were female, and 72% were under the age of 15. Interactive education was delivered through group discussions, which effectively increased participants’ knowledge of proper dental hygiene and the importance of a healthy diet. The results of the dental check-ups revealed that 41% of students had cavities, with some reporting pain. These findings underscore the need for ongoing education and regular check-ups to prevent more serious dental health issues. This program not only raises awareness of proper dental care but also fosters a generation that is more conscious of their oral health. This, in turn, supports sustainable tourism in Pangandaran, where improved public health can enhance the region’s appeal and create a more welcoming environment for both tourists and local communities.